The Effect Of Reader’s Theater Strategy On Students’ Skills In Writing Recount Text - Kiki Rizki Amelia; Rekha Asmara; Dewi Sartika (Edu-Ling: Journal of English Education and Linguistics, 2022)
Writing is an effective tool de develop communication for students. By writing, students can explore everything to deliver to others. As a result, the purpose of this study was to look into the effect of the reader's theater strategy on improving students' writing skills when writing recount text. This was a pre-experimental study. This study's sample consisted of eighth-grade students from MTs Pidua Meranjat. The information was gathered using a written test and analyzed using a paired sample t-test. The findings revealed that the t-obtained (5.228) was higher than the t-table (0.692) at a significant level of p-value below 0.5. It meant that there was a significant improvement in writing recount text after having taught using the reader’s theater strategy. In conclusion, the Reader’s Theater strategy affected students in writing recount text because it offers a fun way of learning where students must complete a story by recreating the script by characterizing the text that was guided by its strategy.